The Use of Picture Story Method in Character Building for Reading in 5-6 Years Old Children at PAUD Setia Pontianak - Susana, Erika; Halida; Lukmanulhakim (Journal of Early Childhood Development and Education, 2024)
This research aims to describe the use of the illustrated story method in forming characters who love reading in children aged 5-6 years at PAUD Setia Pontianak. The research method used is a descriptive method in the form of qualitative research. The subjects in the research were teachers and early childhood children on Jalan Parit Pangeran Gang Keto, Siantan Hulu, North Pontianak District, Pontianak City. The data collection techniques used in this research were participant observation, interviews and documentation. The results of the research show that: 1. Preparation for using the picture story method in forming characters who like to read in children aged 5-6 years at PAUD Setia Pontianak. Preparation is carried out by preparing the RPPH first and then determining the theme of the picture story book. 2. Implementation of the use of the picture story method in forming characters who like to read in children aged 5-6 years at PAUD Setia Pontianak, the teacher tells stories in front of the class while carrying a picture story book. 3. Evaluation of the use of the picture story method in forming the character of reading in children aged 5-6 years at PAUD Setia Pontianak to determine the level of achievement of children's development in the form of notes used to measure the level of children's success, namely written reports, checklists and portfolios in the form of notes regarding children's behavior when listening to stories written factually and truthfully. The researcher suggests that teachers preparing story books should be prepared more carefully and the selection should be more precise. The implementation of using the picture story book method should not be like lecturing. The atmosphere when telling stories can be brought into the story so that it is more enjoyable. Evaluations should be more varied to make it easier for teachers to assess. child. The implications of using the picture story method using books in forming characters who like to read in 5-6 year olds at PAUD Setia Pontianak. Teachers can apply the picture story method using books which is more exciting so that children will be happier when they hear the stories being told.